The construction of science and technology innovation policy design framework—take Shandong Province as an example. (28th March 2020) - Jia, Yongfei; Liu, Chang; Yin, Chong; Zhu, Qing
Abstract : Purpose: Under the background of economic and technological globalization, all countries will pay attention to science and technology innovation policies. At this time, the era of innovation policy plays an important role. In order to thoroughly implement the spirit of the 19th National Congress of the Communist Party of China, earnestly innovate development concepts and strengthen the key supporting role of scientific and technological innovation for social development. Design/methodology/approach: The research will make an in-depth study on the policy of scientific and technological innovation, take the change trend of the number of laws and regulations and the analysis of the basic content as the entry point, and classify it from five different aspects, such as the policy of scientific and technological system and mechanism, the policy of financial guidance, the policy of technological innovation of enterprises, the policy of scientific and technological talents, and the policy of intellectual property. Findings: Through the comparison of the development history of science and technology policies at home and abroad, the development history of science and technology innovation policies under the special national conditions of China is obtained. Combining with the relevant basic theories of science and technology innovation system, designing from the publishing department, main content, and implementation subject, constructing a synergistic science and technology innovation system of "government, industry, university and research, " and forming an "integration of supply and demand" technology innovation framework will guide the development of China's science and technology innovation in the future. Originality/value: The authors construct the policy framework of science and technology collaborative innovation based on the concept of science and technology innovation policies. The framework has realistic significance for its future development.